Tribological Properties of Nano-dimensional Systems Containing Carbon Surfaces - A.V. Khomenko; N.V. Prodanov; К.P. Khomenko; D.S. Troshchenko (Журнал нано- та електронної фізики)
We review tribological properties of boundary films of hydrocarbons and water confined between atomically smooth and rough surfaces. Both theory and experiment show that ultrathin film of liquid with thickness less than six molecular diameters restricted in small volumes is solid-like. Such a state is characterized by the decrease of mobility of molecules related to the increase of relaxation times and decrease of the diffusion coefficient. Additionally, quasidiscrete layers of molecules appear and in-plane ordering of the layers occurs. Atomic-scale roughness of the walls destroys the order of the molecules. We also describe experimental studies of friction of graphite at the atomic level. The experiments suggest a principal possibility of superlubricity for the tungsten tip of friction force microscope sheared on the surface of graphite. A possible explanation of this phenomenon consists in the existence of the graphite nanoflake attached to the tip. However, reliable confirmation of this hypothesis is absent in the literature. We also review methods of the graphene preparation through exfoliation of a graphite sample and formation of defects in graphene as a result of its irradiation by different particles. We describe the experimental method of measurement of friction of metallic nanoparticles sliding on the surface of graphite. We consider basic advantages of this approach compared to the known methods and friction duality in these systems. The review indicates the necessity of further comprehensive theoretical study of friction of metallic nanoparticles adsorbed on atomically smooth surfaces.